Table of Content - -, (Journal of medical and pharmaceutical sciences, 2025)
Table of Content:1. Evaluation of the Quality of Health Services at Turkish Palestinian Friendship Hospital in Gaza Strip, Palestine: Patients’ PerspectiveDr. Eman Suliman Hassouna2. The Role of Mobile Health (mHealth) in Enhancing Healthcare Delivery in Remote Areas: A Systematic ReviewMuhammad Obaid M. Alotaibi
Keywords: Journal of Medical and Pharmaceutical Sciences